Fishermen's Entrepreneurial Activities for Coastal Development Innovation in West Sumatra - Zamzami, Lucky (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
This study focuses on the role of fishermen in the development of ecotourism through entrepreneurial activities on Pasia Tiku Beach. The research aims to understand the role and contribution of fishermen in maintaining environment-based tourism. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews, participatory observations, and documentation. The research informants consisted of local fishermen, ecotourism managers, and tourists. The results of the study show that fishermen not only play a role as environmental guardians but also as tour guides and local economic actors through entrepreneurial activities carried out. The involvement of fishermen in ecotourism activities has been proven to increase environmental awareness and provide significant economic benefits to the community. The results of this study can contribute to the development of a sustainable ecotourism model involving local communities, especially fishermen as the main actors. In addition, the results of this study can be a reference for the government and other stakeholders in formulating ecotourism development policies and strategies’ or if it will change the face of the case law as it currently stands.